THE USE OF “FLIPPED CLASSROOM” TECHNOLOGY IN TEACHING FOREIGN LANGUAGE FOR SPECIFIC PURPOSES - Конопляник, Л.; Мельникова, K. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
In the context of globalization and rapid development of information technologies, which have become an integral part of human life today, there is a great interest in the use of modern ICT in the field of higher education, as well as there is an urgent necessity to introduce new teaching methods and technologies that meet the demands of modern society and the needs of the students belonging to the digital generation. Nowadays the “flipped classroom” technology is becoming more and more popular in educational establishments. The paper deals with topical issues of implementing the “flipped classroom” technology in the educational process of a technical higher school. The study theoretically substantiates the essence of the given technology and the possibility of its application for effective students’ preparation for future professional activity; describes the general features of the given technology; generalizes a set of advantages (e.g., flexible schedule; consideration of students’ individual characteristics; development of students’ responsibility for learning outcomes, etc.) and outlines the difficulties of its implementation in the educational process of a higher school (e.g., a great amount of time needed to create online resources, difficulties with accessing the Internet, etc.); reveals the differences between the traditional and “flipped” classes and the role of a teacher in them. The need for teachers to be aware of their role and functions is emphasized when they leave the leading role in favour of closer collaboration and joint contribution to the learning process. During such training, the teacher is transformed from a translator of the educational material to a facilitator, whose task is to support students in achieving educational goals, encourage, stimulate and help them solve educational tasks. The paper also notes that in order to implement this technology effectively the important tasks for the teacher is a properly developed methodological support for students’ self-study by using Internet resources and the proper control over the completion of the tasks. The authors have demonstrated the peculiarities of the use of “flipped classroom” while teaching “Foreign Language for Specific Purposes” at the National Aviation University, determined the need for its introduction, as well as they have summarized the impact of this technology to improve the quality of teaching and students’ training for the professional activity